Theoretical Insight into the Structure, Energetic Property and Thermal Stability of C6N6H12 Cages - Zhang, J.; Chen, G.; Gong, X. (My University, 2016)
Recent theoretical studies have identified carbon-nitrogen cages are potentially stable high energy density materials. Two such C6N6H12 cages were proposed and investigated using the density functional theory comparison with two similar common cage compounds hexaazaisowurtzitane and cubane. The structure and energetic property were researched. Stability is approached in two ways: (1) stability of one isomer versus another based on the relative energy, (2) thermal stability determined by the bond breaking energies. Taking into consideration of the stability and detonation performance, two C6N6H12 cages may be candidate as potential high energy density compounds.
Keywords: Cage; Heat of formation; Strain energy; Detonation performance; Stability